The tumor suppressor RASSF8: A WAVE interaction partner controlling migration and cohesion of invasive border cells in Drosophila - Mila Y. Höhne; Wiebke Milani; Kirsten Ramlow; Sven Bogdan (Proceedings of the National Academy of Sciences, 2025)
Collective cell migration is a key driver of tissue morphogenesis and cancer invasion. Here, we identified the tumor suppressor Ras association domain-containing protein 8 (RASSF8) as a WAVE interactor required for border cell migration. RASSF8 colocalizes with F-actin and cell adhesion molecules at border cell– border cell contacts. Loss of RASSF8 function results in border cell cohesion defects, a phenotype associated with changes in the localization of the Echinoid (Ed) and Coracle (Cora). Cell-type-specific RNA interference (RNAi) experiments suggest that cohesion defects are caused by changes in localization of Ed rather than E-cadherin. Gain-of-function experiments further revealed reciprocal functional interactions between RASSF8 and WAVE controlling collective border cell movement. Thus, we propose a dual function of RASSF8 in coordinating border cell cluster behavior. RASSF8 is thought to regulate the collective movement of border cells by restricting WAVE function, while it controls the epithelial cluster integrity by regulating cell–cell adhesion and septate junction molecules such as Ed and Cora.